THE USE OF “SAY HEY GOOGLE” FOR PRONUNCIATION ACCURACY TO PRESENT DIALOGUES IN A SPEAKING CLASS - Rahayu, Endang Yuliani; Purwanto, Sugeng (Proceeding SENDI_U, 2020)
Pronunciation has been always a problem especially for students of English as a foreign language. Thisis because the phonological system of the native language differs significantly from that of the target language.The current study offers a new way of pronunciation feedback by using “Say Hey Google”. On pronouncing aparticular word on the application (Smartphone), Hey Google will reproduce the word in writing. When HeyGoogle writes the word correctly, it means that the pronunciation is correct and intelligible according to thereceived standard of pronunciation. The findings show that the subjects (consisting of 22 students of Semester 1FBIB, Unisbank) varyingly managed to use Hey Google as pronunciation feedback device. Some words whichthey failed to correctly pronounce were pronounced by the lecturer to get the correct pronunciation.Surprisingly, the majority of the students have positive attitudes and perception of the device (Hey Google).